Tsunami Risk Mapping of Lumajang District Using Geographic Information System (GIS) - Amien Widodo; Dwa Desa Warnana; Juan Pandu Gya Nur Rochman; Firman Syaifuddin; Erik Sapta Perbawa; Ary Iswahyudi; Wien Lestari (IPTEK Journal of Proceedings Series, 2017)
Indonesia lied among the three of world major plates so that several districts along the southern coast of Java Island were vulnerabled to the tsunami including Lumajang. South coast of Lumajang had high population density and settlements and high levels of government and economic activity. Therefore, it is necessary to know the level of insecurity and vulnerability to the tsunami in order to be utilized as input of mitigation data for the preparation of regional spatial plans (RTRW) based on tsunami risk level. The objective of this research is to arrange the regional risk map for tsunami in Lumajang Regency using Geographic Information System (GIS) through approach of insecurity and vulnerability analysis of tsunami. The insecurity rate is analyzed based on seismicity map and run-up data of tsunami event in Lumajang District. Vulnerability approach used multicriteria such as land elevation, slope, coastal morphometry, land use, distance from the coast and distance from the river. The methodology that was used included data collections of both primary and secondary data such as satellite imagery of earth map, Lumajang statistical data. Each vulnerability data variable was processed to result a weighting and scores that its become the parameters for making a regional tsunami vulnerability map. The results showed three level of risks in five subdistricts that directly adjacent to the Southern Coast such as Yosowilangun, Kunir, Tempeh, Pasirian, and Tempursari. The high tsunami risk which covered almost along the coast, the ramps morphology, without any protective vegetation and human activities at the site while the medium of tsunami risk which were in areas with elevation more higher than the coastal and the low of tsunami risk had variations of topography, quite far from the coast and less human activities.